Penerapan Ilmu Tajwid Pada Tpq Miftahul Huda Di Dusun Jatisari Desa Krenceng, Kecamatan Kepung Kabupaten Kediri - Syari Fatul Umah; Khoiruzzaim Kurniawan (LP3M IAIFA Kediri, 2021)
This research is motivated by the importance of understanding tajwid because understanding Tajweed is seen as enough to make TPQ children aware of applying tajwid reading of the Koran, so Tajweed is a scientific discipline that has certain rules that must be guided in the pronunciation of the makhraj letters. As well as the relationship of each letter to the letter before and after it in the way it is pronounced. So studying Tajweed is highly recommended for all Muslims so that they can read the Qur'an smoothly, well and correctly. Because reading the Koran is not just reading, but reading it must be correct in accordance with the rules set. Therefore, in order to know the correct procedure for reading the Qur'an, one must first master the main points of discussion in Tajweed Science.